MANAJEMEN NUTRISI PADA PASIEN TUBERKULOSIS PARU UNTUK MENINGKATKAN INDEKS MASSA TUBUH (IMT)DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Dewi, Febri Masitah; Susyanti, Deni; Gea, Handerman Vitu (SINERGI : Jurnal Riset Ilmiah, 2025)
Pulmonary Tuberculosis (TB) is an infectious disease that attacks the lungs and often causes nutritional status disorders such as significant weight loss to reduced body mass index (BMI). This study aims to provide an overview of the implementation of nutritional management in pulmonary tuberculosis patients to increase Body Mass Index (BMI) at Putri Hijau Class II Hospital. The method used in this study is descriptive research using case studies on 2 patients using a medical surgical nursing care approach that includes assessment, diagnosis, planning, implementation, and evaluation of nursing, with inclusion criteria namely patients suffering from pulmonary tuberculosis, with a BMI of 18.5 and who experience nutritional deficit problems. This study uses a nursing implementation approach that includes identifying nutritional status: Oral hygiene management and providing diet education. The results of this study showed that after 3 days of implementation, there was an increase in BMI in both patients, where previously patient 1 had a BMI of 17.7 and patient 2 had a BMI of 16.9 which increased to 18.1 and 17.3, respectively. Body weight increased by 1 kg, oral hygiene improved, and knowledge increased. The implementation of nutritional management has been proven to have a positive impact in improving the nutritional status of pulmonary tuberculosis patients